Key Decision Makers and Actors in Selected Newborn Care Practices: A Community-Based Survey in Northern Uganda - Mukunya, David; Nankabirwa, Victoria; Ndeezi, Grace; Tumuhamye, Josephine; Bruno Tongun, Justin; Kizito, Samuel; Napyo, Agnes; Achora, Vincentina; Odongkara, Beatrice; Arach, gnes Anna; Tylleskar, Thorkild; Tumwine, James K. (International Journal of Environmental Research and Public Health, 2019)
Knowledge of key decision makers and actors in newborn care is necessary to ensure that health interventions are targeted at the right people. This was a cross-sectional study carried out in Lira district, Northern Uganda. Multivariable logistic regression was used to determine factors associated with mothers being the key decision maker regarding where to give birth from and when to initiate breastfeeding. Fathers were the key decision makers on the place of birth (54.3%, n = 505) and on whether to seek care for a sick newborn child (47.7%, n = 92). Grandmothers most commonly bathed the baby immediately after birth (55.5%, n = 516), whereas mothers and health workers were common decision makers regarding breastfeeding initiation. Predictors for a mother being the key decision maker on the place of birth included: Mother having a secondary education (AOR 1.9: 95% C.I (1.0–3.6)) and mother being formally employed (AOR 2.0: 95% (1.5–2.9)). Mothers, fathers, grandmothers, health-workers, and traditional birth attendants were the most influential in the selected newborn care practices. Programs that aim to promote newborn care need to involve husbands, grandmothers, and health workers in addition to mothers.
Keywords: Newborn; Neonatal; Implementation; Influencers; Actors; Decision-making; Uganda; Post-conflict; Behavior